Bonsoir,
A= 2(1 - 2x) + 3(x - 1)
A= 2- 4x + 3x -3
A= - x - 1
B= -3(5x - 4) - 2(x + 2)
B= -15x + 12 - 2x + 4
B= -17x + 16
C= 4x(1+x) - 3x(2x-4)
C= 4x + 4x² - 6x² +12x
C= 16x - 2x²
D= -5x ( -x-1) - 2x(x + 4)
D= 5x² + 5x - 2x² - 8x
D= 3x² - 3x
E= 2x (3x² - 4x - 5) + 6x (x³ - 5x² + 8x - 1) -4x(1-x)
E= 6x³ - 8x² - 10x + 6x⁴ - 5x³ + 48x² - 6x -4x + 4x²
E= 6x⁴ - x³ - 44x² - 20x
F= 6x²(1 - x² + x) - 7x(3x - 2) +5x - 8
F= 6x² - 6x⁴ + 6x³ - 21x² - 14x + 5x - 8
F= - 6x⁴ + 6x³ - 15x² - 9x -8
J'espère t'avoir aidé ! ^^